Moving beyond the riverine barrier vicariant paradigm. Issue 12 (8th June 2020) - Naka, Luciano N.; Pil, Maria W.
Abstract: One of the main goals of evolutionary biology is to understand the processes behind current patterns of biodiversity. Shared geographic distributions among unrelated species may result from a common history, providing a unique opportunity to assess the evolution of the landscape and the origins of biodiversity. Until recently, vicariance prevailed as the main evolutionary model to be tested, and the riverine barrier hypothesis the null model for taxa with river‐bounded distributions. In recent years, however, multispecies comparative approaches have unveiled idiosyncratic scenarios among codistributed species, suggesting that rivers may or may not play a role in the speciation process. In a From the Cover article in this issue of Molecular Ecology, Kopuchian et al. (2020) explore predictions of the riverine barrier hypothesis in a major subtropical river system, evaluating the degree of mitochondrial and nuclear genomic differentiation in seven bird species with allegedly morphological differentiation across the Paraná‐Paraguay river system. The authors show that in only one case, the genetic differentiation was concordant with the river. Interestingly, pairs presented disparate divergence times and/or distinct demographic histories. In most cases, putative contact zones broadly coincided with the transition of different ecoregions, such as the Espinal/Chaco ecological ecotone. These findings argue against the role of the Paraná‐Paraguay river system as a major biogeographic barrier and highlight the need to explore the role of ecology in species diversification. Here, we feature different perspectives for studying the processes governing species divergence and suggest a basic protocol to advance the study of riverine barriers.